Implementation of the futile therapy concept in the conditions of Polish intensive care units - a description of five cases - Jóźwiak, Aleksandra; Rutyna, Rafał; Fijałkowska-Nestorowicz, Anna; Bielacz, Magdalena; Zukow, Walery; Kotlińska-Hasiec, Edyta (Journal of Education, Health and Sport, 2019)
The concept of futile therapy is an attempt to solve the problem that arose on the sidelines of the success of intensive therapy. Both the theoretical bases of futile therapy and the ways of implementing it on the hospital ward raise much controversy. This paper aims to present practical aspects of the implementation of the concept of futile therapy in Polish intensive care units. Increasingly, the ICUs are struggling with prolonged maintenance of organ functions that do not bring therapeutic benefit to the patient (futile therapy). In 2014, under the leadership of Professor Kübler, guidelines for ICUs were established for dealing with the ineffectiveness of maintaining organ functions in patients incapable of providing informed declarations of will. As part of the implementation of futile therapy, it is possible to either withdraw from conducted therapies or withhold from taking new ones. The guidelines are the first official document in Poland containing instructions on how to proceed in futile therapy. The constantly increasing number of futile therapy protocols suggests that the guidelines, despite not being part of the common law, significantly facilitate the work of ICU doctors. In everyday practice, doctors face the difficulty of distinguishing between the situation in which the same therapeutic techniques either aid the treatment of the patient or unnecessarily prolong the process of dying. The futile therapy can take up many forms, this article focuses on practical aspects of the implementation of futile therapy in five different clinical cases.